Combination of photoelectrocatalysis and ozonation: A novel and powerful approach applied in Acid Yellow 1 mineralization - Bessegato, Guilherme Garcia [UNESP]; Cardoso, Juliano Carvalho [UNESP]; da Silva, Bianca Ferreira [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier, 2016)
Photoelectrocatalytic oxidation (PEC) is known to be a powerful technique employed with the aim of promoting organic degradation. Its efficiency is nonetheless found to be dramatically decreased when applied in highly concentrated effluent treatment owing to the reduced transparency which minimizes the photons reaching the semiconductor surface. In light of that, the present work seeks to describe a novel combination of photoelectrocatalysis and ozonation (O3+PEC) techniques, aiming at achieving a faster decolorization of a highly concentrated solution and a higher rate of mineralization. The Acid Yellow 1 dye (AY1), widely used in cosmetics was chosen as a colorful solution model. TiO2 nanotubes electrode was used as photoanode in an annular bubble reactor operating at 2.0V with UV-B irradiation in the presence of 1.25×10-4molmin-1 of O3. The main factors interfering in the O3+PEC process were optimized through UV/vis spectrophotometry, total organic carbon (TOC) and mass spectrometry measurements. After 20min of treatment using the combined system, 100% of decolorization was observed while a total mineralization was seen following 60min of treatment even in effluents containing 100ppm AY1. Concomitantly, the combined system (O3+PEC) showed higher decolorization rate constant and lower energy consumption compared to the other techniques, showing that O3+ PEC is a successful, efficient and cost-effective alternative for water treatment.
Keywords: Catalytic ozonation; Dye degradation; Ozone assisted Photoelectrocatalysis; Photoelectrocatalytic oxidation